Experimental Study on Mechanical and Electrical Properties of PV-PVC Composites - Lanlan Zhang; Yingying Zhang; Meng Wu; Junhao Xu; Jigang Xue (Advances in Civil Engineering)
Based on BIPV, the idea of flexible amorphous silicon solar cell (PV) and PVC membrane composite was put forward. In this paper, the influence of composite mode and force form is mainly investigated. The mechanical and electrical properties of PV-PVC composite under uniaxial and cyclic tension are obtained. The main results show that the tensile strength of PV-PVC composite is basically the same as that of PVC membrane. Compared with PVC membrane, the modulus of elasticity of PV-PVC composite under cyclic loading is significantly increased, while the residual strain and the area of hysteresis loop are significantly reduced. The difference in mechanical properties of different off-axis angles is significantly reduced. Under the stress level of common design strength of PVC membrane materials, solar cells can play a good photoelectric effect. This paper provides an important reference for the realization of membrane structure photovoltaic integration.